(3GdMLI aj SQbGJ GHf MLIs - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s; (3CHh HcQ Hf Ydj Hf YHO Gddg GdMehj GdCRQGQj, Jbj GdOjf GHf MLI,J (B837 (3g` s
(3ChdgG (B:s
(3hHYO(B: (3adeG fRd HeUQ eG fRd ef GdeUGH ef ONhd GHf MLI GdeTFhe EdjgG hEPG gh bO HOd fYeI Gddg JYGdi HGdcaQGf hNGf eYGedJg hGddg dG jMH cd NhGf, Ef PcQ GdeJbOehf GSJWGd HdSGfg s
(3BNQgG (B:s
(3hdg(B: (3TQjaqj JfGhdg TQja SHGfj efg HGdMW GdXQja heG Wdfj hCjf dj GUWHGQ hbdHj bO Jhdi HGdTQjaj s
(3GfXQ CjVkG OjhGf GHf MLI GdMehj h Lfi GdLfJjfs
(3fSNI MOjKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B67s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B253 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B631s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs